Pengaruh Variasi Produk dan Sistem Penjualan terhadap Kinerja Pemasaran UMKM di Kecamatan Kampa - Prima Yodes Pratama; Nany Librianty; Samsurijal Hasan; Rizqon Jamil Farhas; Rinda Fithriyana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The problem in this research is the low variety of products and sales systems on the marketing performance of MSMEs in Kampa sub-district. This research aims to determine the effect of product variations and sales systems on the marketing performance of MSMEs in Kampar District. The variables used in this research are product variations and sales systems as independent variables and marketing performance as the dependent variable. This research is quantitative research. The data source in this research is primary data where the data collection method uses a questionnaire method which was distributed to all MSMEs in Kampa District which were the research subjects, totaling 53 respondents. The research population for MSMEs in Kampa sub-district is 61 MSMEs. The sample for this research consisted of 53 MSMEs. The results of this research show that product variations have a positive and significant effect on marketing. The sales system variable has a positive and significant influence on marketing performance. Based on the calculated product variations and sales systems can jointly influence the marketing performance of MSMEs in Kampa District